Bringing the Real World Into Developmental Science: A Commentary on Weber, Fernald, and Diop (2017). Issue 6 (10th July 2018) - Morelli, Gilda; Bard, Kim; Chaudhary, Nandita; Gottlieb, Alma; Keller, Heidi; Murray, Marjorie; Quinn, Naomi; Rosabal‐Coto, Mariano; Scheidecker, Gabriel; Takada, Akira; Vicedo, Marga
Abstract : This article examines the parent intervention program evaluated by Weber et al. (2017) and argues that there are scientific and ethical problems with such intervention efforts in applied developmental science. Scientifically, these programs rely on data from a small and narrow sample of the world's population; assume the existence of fixed developmental pathways; and pit scientific knowledge against indigenous knowledge. The authors question the critical role of talk as solely providing the rich cognitive stimulation important to school success, and the critical role of primary caregivers as teachers of children's verbal competency. Ethically, these programs do not sufficiently explore how an intervention in one aspect of child care will affect the community's culturally organized patterns of child care.